StAGE: stellar archaeology-driven galaxy evolution - Bosi, Michele; Lapi, Andrea; Boco, Lumen; Alvarez, Carlos A.; Cueli, Marcos M.; Antinozzi, Giovanni; Behiri, Meriem; Giulietti, Marika; Massardi, Marcella; Spera, Mario; Bressan, Alessandro; Baccigalupi, Carlo; et al. (The astrophysical journal, 2025)
We build a semiempirical framework of galaxy evolution (dubbed StAGE) firmly grounded on stellar archaeology. The latter provides data-driven prescriptions that, on a population statistical ground, allow us to define the age and the star formation history for the progenitors of quiescent galaxies (QGs). We exploit StAGE to compute the cosmic star formation rate (SFR) density contributed by the progenitors of local QGs, and show it to remarkably agree with that estimated for high-z dusty star-forming galaxies which are faint/dark in the near-infrared (NIR), so pointing toward a direct progenitor-descendant connection among these galaxy populations. Furthermore, we argue that by appropriately correcting the observed stellar mass density by the contribution of such NIR-dark progenitors, StAGE recovers a SFR density which is consistent with direct determinations from UV/IR/radio surveys, so substantially alleviating a longstanding tension. Relatedly, we also show how StAGE can provide the average mass and metal assembly history of QGs, and their redshift-dependent statistics. Focusing on the supermassive black holes (BHs) hosted by massive QGs, we exploit StAGE to reconstruct the average BH mass assembly history, the cosmic BH accretion rate density as a function of redshift, and the evolution of the Magorrian-like relationship between the relic stellar and BH masses. All in all, StAGE may constitute a valuable tool to understand via a data-driven, easily expandable, and computationally low-cost approach the coevolution of QGs and of their hosted supermassive BHs across cosmic times.